Community-Based Psychosocial Treatment Has an Impact on Social Processing and Functional Outcome in Schizophrenia - Varga, Eszter; Endre, Szilvia; Bugya, Titusz; Tényi, Tamás; Herold, Róbert (Frontiers in Psychiatry, 2018)
Schizophrenic patients have serious impairments in social cognition, which often persists after significant reduction in clinical symptoms. Community-based psychosocial treatments aim to recover social functioning for mentally ill individuals. Our aim was to examine prospective changes in social cognition and functional outcomes in two groups of schizophrenic patients involved in two forms of community-based psychosocial treatments namely case management (CM) and community-based club (CC) compared to a matched, treatment as usual (TAU) group of patients. We hypothesized that CC and CM groups would exhibit better functional and social cognitive outcomes after a six-month long psychosocial treatment period. Seventy-five patients participated either in CC, CM or TAU. Both CC and CM took part in community-based psychosocial treatment programs including trainings, such as communication and assertiveness trainings. In addition, CC provided group therapeutic treatments and a continuously available day care where patients had the possibility to participate in various social interactions. All participants were in remission, and on maintenance antipsychotic treatment. Participants were assessed on all study variables at two time points: baseline and after 6 months with a battery of questionnaires that examined affective face perception, affective prosody perception, pragmatic language comprehension and ToM. Our results showed that functional outcomes improved significantly in the CC as well as in the CM groups, in contrast to the TAU group. While analysing summary scores of social cognition, it was found that only the CC group increased its performance in social cognition. In addition, a significant between-group difference in social cognitive function was found after 6 months between the three groups, with the CC group performing best. When investigating associations between changes in social cognition and changes in functional outcomes during a six-month long treatment period, we found significant correlations between the two variables both in the CC and in the CM groups. Based on our results, we suggest that a rich interpersonal network and social support have highly beneficial effects on social cognition and we would like to emphasize the necessity of offering community-based psychosocial treatments beside antipsychotic medications as early as possible as a crucial part of the complex therapy of schizophrenia.